2017
DOI: 10.7448/ias.20.1.21594
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of HIV self‐testing compared to standard HIV testing services: a systematic review and meta‐analysis

Abstract: Introduction: HIV self-testing (HIVST) is a discreet and convenient way to reach people with HIV who do not know their status, including many who may not otherwise test. To inform World Health Organization (WHO) guidance, we assessed the effect of HIVST on uptake and frequency of testing, as well as identification of HIV-positive persons, linkage to care, social harm, and risk behaviour.Methods: We systematically searched for studies comparing HIVST to standard HIV testing until 1 June 2016. Meta-analyses of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
334
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 323 publications
(354 citation statements)
references
References 29 publications
17
334
1
2
Order By: Relevance
“…Consistent with previous reports , all distribution models had high male participation in each country. Strategies that provide men with greater coverage of HIV testing and care are urgently needed both to address the disproportionately high testing gap and mortality from HIV in men, and also to reduce risk of onward transmission of HIV .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reports , all distribution models had high male participation in each country. Strategies that provide men with greater coverage of HIV testing and care are urgently needed both to address the disproportionately high testing gap and mortality from HIV in men, and also to reduce risk of onward transmission of HIV .…”
Section: Discussionmentioning
confidence: 99%
“…Peak HIV prevalence for men in southern Africa is now in the 40‐ to 49‐year‐old age‐group , with older men among least likely to have accessed standard HIV testing services . Older men appear relatively receptive to HIVST, however, as evidence by the data reported here as well as from implementation studies from Kenya, Lesotho and Zimbabwe . For adolescent boys, HIVST can provide the first opportunity to test without fear of judgement from parents and healthcare workers , explaining the high uptake among this age group when HIVST was offered at community level.…”
Section: Discussionmentioning
confidence: 99%
“…A key concern with self‐testing is whether self‐testers would seek HIV treatment . This study demonstrated a noteworthy 100% linkage to HIV treatment; the national linkage rate is 31% .…”
Section: Discussionmentioning
confidence: 99%
“…HIV self‐testing (HIVST) can increase HIV testing coverage and frequency . Several studies in Malawi have shown HIVST to be highly acceptable and able to reach first‐time testers, young people (aged 16 to 25), men and couples and partners , with acceptable linkage into facility‐based services when combined with facilitated linkage strategies .…”
Section: Introductionmentioning
confidence: 99%